2004
DOI: 10.1152/japplphysiol.00707.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the volume and intensity of exercise training on insulin sensitivity

Abstract: Physical activity enhances insulin action in obese/overweight individuals. However, the exercise prescription required for the optimal enhancement is not known. The purpose of this study was to test the hypothesis that exercise training consisting of vigorous-intensity activity would enhance insulin sensitivity more substantially than moderate-intensity activity. Sedentary, overweight/obese subjects (n = 154) were randomly assigned to either control or an exercise group for 6 mo: 1) low-volume/moderate-intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
347
14
30

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(421 citation statements)
references
References 27 publications
30
347
14
30
Order By: Relevance
“…The finding that walking activity status was not associated with fasting insulin levels is in contrast to other studies (Houmard et al 2004, Mayer-Davis et al 1998). …”
contrasting
confidence: 99%
“…The finding that walking activity status was not associated with fasting insulin levels is in contrast to other studies (Houmard et al 2004, Mayer-Davis et al 1998). …”
contrasting
confidence: 99%
“…Physical activity can reduce muscle insulin resistance [20,21]; however, studies have also shown that physical activity is associated with a lower intrahepatic fat content [22], and that intrahepatic fat content is associated with hepatic insulin sensitivity [23,24]. Consequently, a differential effect of physical activity on progression to diabetes in individuals with i-IFG and i-IGT could be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Houmard et al [25] investigated whether vigorous-intensity exercise training would improve insulin action to a greater degree than moderate-intensity training. The participants in this study [25] comprised 154 sedentary, overweight men and women with pre-diabetes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The participants in this study [25] comprised 154 sedentary, overweight men and women with pre-diabetes (i.e. dyslipidaemia considered as a pre-diabetic state).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation